The Repicci II(®) Unicondylar Knee Arthroplasty: 9-year Survivorship and Function - O’Donnell, Turlough (Springer-Verlag, 2010)
BACKGROUND: Unicompartmental knee arthroplasty (UKA) is a recognized procedure for treatment of medial compartment osteoarthritis. UKA using minimally invasive surgery (MIS) has the theoretical advantage of less bone resection and quicker rehabilitation. Whether the function of patients with UKA compares with that of patients with conventional TKA is unclear. QUESTIONS/PURPOSES: We determined (1) the length of stay and complications associated with a short-stay MIS protocol; (2) whether MIS techniques allow for accurate positioning of the implant and alignment of the limb; (3) the change in functional scores; (4) the revision rate, reasons for revision, and survival of this implant. PATIENTS AND METHODS: We prospectively followed 100 patients who had 114 UKAs. All completed an International Knee Society (IKS) score preoperatively, at 1 year, and at last followup. We determined survivorship. Minimum followup was 5.2 years (mean, 7.4 years; range, 5.2–9 years). RESULTS: Mean length of stay was 1.2 days, with 41% discharged the same day. The perioperative complication rate was 6%. The mean IKS score improved from 77 to 93 and was 86 at last followup. The mean hip-knee-ankle axis changed from 6° varus to 1.7° varus. Twenty-two patients underwent a revision procedure at a mean 6.2 years after the index procedure. Survivorship of the prosthesis was 78% at 9 years. CONCLUSIONS: The short-stay protocol was not associated with a high perioperative complication rate. This technique is associated with improvement in function and restoration of limb alignment, allowing accurate positioning of the implant. Compared with other reports of survival of UKA, this implant had a lower survivorship and increased revision rate. LEVEL OF EVIDENCE: Level IV, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence.